O ateísmo de Richard Dawkins nas fronteiras da ciência evolucionista e do senso comum - Franco, Clarissa de (2014)
The object of study is the main Richard Dawkins ideas of atheism and this reception on the brasilian atheists. Dawkins is one of the leading publishers and militant atheist movement today, and despite his public facet - released worldwide on websites and in books of recognized success - there are debates of the author , pertaining to academic spaces and restricted to scientists, who do not always have congruent to its exhibitions and public defenders . Internally the walls of science, Richard Dawkins can not find full verification and corroboration of some central points of his theory that seem to support its public arguments of atheism, such as the theory and the concept of memetic and selection gene, ideas presented to the lay public one of his most famous books, The Selfish Gene (2001a [1976]) and maintained publicly with the status of consolidated science. We assume that the figures of scientist and militant atheist from Dawkins mingle in front of the public imagination, which tends to lead his followers to understand atheism as a more legitimate and true way that religious, being interpreted that as a way to free choice and the latter undergoes a indoctrination. We believe, however, that atheism can be understood as subject to natural cognitive mechanisms, as religion. We take into account the political scene today is favorable to atheists, since we observed a phenomenon we call "moral atheists revenge", a reversal of official protection and legitimacy of the state, which has long been welcoming and protecting the speech religious and today happened to be synchronized with atheistics claims, being religious in an outdated and uncomfortable place in the democratic debate. These hypotheses was investigated by means of confrontation between the scientific and public speeches of Richard Dawkins and through a mixed questionnaire (with open and closed questions ) that investigated 1022 atheists, noting whether and to what extent atheism sample follows trends thinking of Richard Dawkins. We observed patterns of response, three groups: Super Atheists, Moderates Atheists and Discrete Atheists. Approximately 30% of the sample declare themselves as followers of the author, and all, nearly 80% have knowledge about any point of the theory of Dawkins